Idiomatic Phrase Processing in Arabic "A Psycholinguistic Study" - Rahmat Hidayat; Ummu Sulaimah Saleh; Ivan Satya; Wildana Wargadinata (International Journal of Language and Ubiquitous Learning, 2023)
Background. The background of this study is to explore psycholinguistic methods to assist Arabic language learners in processing idiomatic phrases more effectively. The focus is on identifying cognitive strategies that can improve the understanding and use of idiomatic phrases in communicative contexts. By solving this problem, it is hoped that learners can become more proficient in the idiomatic aspects of Arabic, improve communication skills, and feel confident interacting with native speakers. Purpose. The main objective of this study is to investigate the psycholinguistic aspects of Arabic idiomatic phrase processing, exploring cognitive strategies in non-native and native learners. The research aims to identify factors that influence comprehension, such as proficiency, culture, and learning experience, focusing on technology-based teaching methods to improve mastery. Method. This study takes a psycholinguistic approach, using a quantitative survey to investigate the processing of Arabic idiomatic phrases. The research involves identifying phrases, designing a survey, and analyzing the data to enhance the insights of understanding, which contributes to the understanding of psycholinguistics. Results. Research shows that learning Arabic in a formal environment has a positive impact on communication skills. The use of Arabic idiomatic phrases in daily life enriches communication. Online resources are dominant in understanding idiomatic phrases. The main obstacle is the difference in Arabic dialects. Psychological factors play an important role in the comprehension of idiomatic phrases and impact on overall Arabic language skills, especially in the context of social and professional communication. Conclusion. His study concluded that learning Arabic in a formal environment, such as school or university, has a great effect on students' speaking ability. The use of idiomatic phrases is also recognized as enriching everyday communication.